Sistem Pakar Identifikasi Penyakit Tanaman Kacang Tanah Menggunakan Metode Fuzzy Mamdani Berbasis Android - Arifandi Wahyu Widianto; Nurul Hidayat; Moch. Cholil Mahfud (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Peanut (Arachis hypogaea L.) is one of important plant commodities after corn and soybean crops. In addition, peanut production in not sufficient needs and often experience crop failure. One of the causes of it is the disease in the peanut itself. To overcome the problem of disease in peanuts done by making disease identification system, thus facilitating the control. The method used is fuzzy mamdani logic and forward chaining, fuzzy logic of Mamdani to determine the value and result of disease diagnosis of the phenomenon, while forward chaining is used for weighting value. After the implementation and testing, obtained the accuracy between experts with the system of 90.00%. From these results can be concluded that the results of the system and experts are aligned and have a positive accuracy.